Study Kelayakan Pembangunan Rawat Inap Puskesmas Ketrowonojoyo Kecamatan Kebonagung Kabupaten Pacitan - Nugroho, Laksono D.; Wulandari, Esti; Setiyo, Anugrah Dwi; Gode, Dicky (Publikasi Indonesia, 2025)
The feasibility of developing inpatient services at Ketrowonojoyo Public Health Center (Puskesmas) must comply with the requirements set in Minister of Health Regulation No. 43 of 2019 and No. 19 of 2024, which mandate adequate office space and service rooms to support the upgrade into an inpatient facility. The main problem lies in the limited facilities that do not yet meet regulatory standards, thus hindering service expansion. This study aims to evaluate the feasibility of establishing inpatient services through a SWOT analysis approach, focusing on infrastructure, human resources, and environmental management. The analysis shows that the Puskesmas requires the addition of seven service rooms to fulfill inpatient criteria, improved access and parking facilities, and upgraded medical waste management systems. Furthermore, the provision of essential human resources is needed, including one physician, six nurses, four midwives, two cleaning staff, four cooks, and two laundry staff, alongside continuous training to enhance medical and non-medical personnel competencies. The findings imply that with the planned additions, Ketrowonojoyo Puskesmas can provide inpatient services comparable in quality to hospitals in Pacitan, thereby improving accessibility and community trust in local health services.